2023
DOI: 10.1152/japplphysiol.00600.2022
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of whole body versus thoracic bioimpedance in relation to ultrafiltration volume and systolic blood pressure during hemodialysis

Melanie K. Schoutteten,
Lucas Lindeboom,
Astrid Brys
et al.

Abstract: In contrast to whole-body bioimpedance, which estimates fluid status at a single point in time, thoracic bioimpedance applied by a wearable device could enable continuous measurements. However, clinical experience with thoracic bioimpedance in patients in dialysis is still limited. In order to test the reproducibility of whole-body and thoracic bioimpedance measurements and to compare their relation with hemodynamic changes during hemodialysis, these parameters were measured pre- and end-dialysis in 54 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…These results were achieved by a consistent electrode configuration and body position of the patients between both sessions. This confirms the results of our previous work, where thoracic resistance was moderately reproducible between two dialysis sessions [ 18 ]. These results strongly suggest that patients have a subject-specific start-point of thoracic bioimpedance.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results were achieved by a consistent electrode configuration and body position of the patients between both sessions. This confirms the results of our previous work, where thoracic resistance was moderately reproducible between two dialysis sessions [ 18 ]. These results strongly suggest that patients have a subject-specific start-point of thoracic bioimpedance.…”
Section: Discussionsupporting
confidence: 92%
“…The linear relationship between the resistance signal at 8 kHz and time implies a constant rate of change. Previously, it has been shown that thoracic bioimpedance signals at low frequencies correlate very strongly w i th ultrafiltration volume [ 5 , 18 ]. The removal of the ultrafiltration volume at a constant rate may explain the linear increase in the resistance signal at 8 kHz.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation